DAMPAK PENGUNGKAPAN SUNSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN DI BURSA EFEK Indonesia (STUDI KASUS PERUSAHAAN TERDAFTAR DI BEI PERIODE 2023-2024) - Imran Rosadi; Agus Salim; Misdayanti Sugiono; Annisa Nur Muslimah (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Sustainability issues are increasingly becoming a major focus in the modern business environment, prompting companies to disclose their social and environmental responsibilities through Sustainability Reports (SRs). This study aims to analyze the impact of sustainability report disclosure on company value among companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. Company value is measured using the Price to Book Value (PBV) ratio, while SR disclosure rate is assessed based on the Global Reporting Initiative (GRI) index. This study uses a quantitative approach with multiple linear regression analysis, with control variables including company size, profitability (ROA), and capital structure (DER).The results of the study show that the disclosure of sustainability reports has a positive and significant effect on the company's value. In addition, company size and ROA were also found to have a significant effect on company value, while DER did not show a significant influence. These findings support legitimacy theory and stakeholder theory, which suggest that sustainability disclosures can increase market confidence and strengthen a company's valuation. The study concludes that SR is not just a compliance document, but a strategic tool to shape investor perceptions and create long-term economic value.